EFFECT OF DIFFERENT COMBINATION OF MACRO AND MICRONUTRIENTS ON THE GROWTH AND YIELD OF GARLIC Allium sativum L - & et al., Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field trial was conducted in Silt loam soil at Al-bu-Farraj, northen Ramadi, 110 km west of Baghdad) , to study the effect of fertilization with macro and micronutrients on growth and yield of garlic ( Allium sativum L.). Randomized complete block design with three replicate was used. Four fertilizer formulations from nitrogen, phosphorus and potassium i.e. A0 (0,0,0) , A1 (80, 80, 80) , A2 (120, 120, 120 and A3 (160, 160, 160) kg.ha-1 were applied. Four concentrations of nutrient solution( B0,B1,B2,B3) (0 , 0.5 , 1 , 1.5) g.L-1 were foliar applied.Results showed no significant difference among treatments regarding plant height. Leaf area , mean head weight and yield were significantly (0.05) increased with rate of application for individual factor and interaction between factors. The combination of fertilizer A2B3 gave higher Leaf area rate of 1166.9cm2.plant-1, and the weight of the head 97.30 g and higher yield of heads was 25.90 Mg.ha-1, compared with less yield 14.30 Mg.ha-1 which was given without A0B0 fertilization. Soil application and foliar spray individually led to significant (0.05) increases in leaves number per plant, while interaction had no significant effect on these trails. For cloves per head only the soil application was significantly active in increasing this trail.